Prevalence and clinical impact of atrioventricular conduction disease in patients with idiopathic pulmonary arterial hypertension. (14th October 2021) - Reddy, A; Nethercott, S L; Teh, W; De Bie, E M D; Pepke-Zaba, J; Sheares, K K; Cannon, J; Taboada, D; Hadinnapola, C; Martin, C A; Toshner, M R
Abstract: Background: Although bradycardia-related sudden death is common in patients with idiopathic pulmonary arterial hypertension (IPAH), the prevalence and prognostic significance of atrioventricular (AV) conduction disease in this patient group is not well-established. Objectives: – Determine the prevalence of AV conduction disorders in patients with IPAH – Investigate the relationship between AV block and functional outcomes and mortality. Method: 12-lead electrocardiograms (ECGs) of patients with IPAH were analysed. Patients were categorised according to the presence or absence of AV block. Demographic, pulmonary haemodynamic, cardiac structural characteristics and expression of genes associated with cardiac conduction were compared and functional and mortality outcomes analysed between groups. Student's t-tests and χ 2 tests were used to compare data. Survival was estimated using Kaplan-Meier analyses. Initial exploratory covariates were included in a univariate analysis and those terms with P-value of <0.1 were then used to generate a Cox proportional-hazards multivariate model. Results: 135 IPAH patients (mean age 55±16 years, 28.1% male) were eligible for analysis. Median follow up was 9 years (interquartile range 4–14 years). AV block was seen in 34.8% of patients with IPAH compared to 10.8% of matched comparators (p<0.001), drawn from patients attending hospital for non-PAH related reasons. IPAH patients with conduction disease were more likely to be older (59±16 vs 53±17 years, p=0.038). AV block was associated with more severe right ventricular (RV) basal dilatation (5.1±1.0 vs 4.3±0.7cm, p=0.013) and worse RV function (fractional area change 26±9% vs 31±9%, p=0.14). Pulmonary haemodynamics, right atrial size and resting and exertional oxygen saturations were not significantly different. Expression of HCN1, HCN2, SCN1B, SCN5A, CAV1, and KCN2 genes in peripheral blood from a subcohort was similar between those with and without AV block. Lower 6 minute walk distances (344±153 vs 408±140m, p=0.035) and worse CAMPHOR scores across all 3 domains were seen in those with AV block (figure 1), and mortality was significantly higher (36.2 vs 13.6%, p=0.002) (figure 2). On multivariate analysis the presence of bundle branch block (BBB) was independently associated with a 2.1-fold increased risk of death (95% CI 1.89–4.85, p=0.045). Conclusions: AV conduction disorders are more prevalent in IPAH than the general population, and are associated with worse prognosis and functional status. Prospective study is required to validate this finding. In our cohort AV block could not be explained by hypoxia, differences in pulmonary haemodynamics nor, in a small subgroup, by differential expression of specific transmembrane ion channels implicated in cardiac conduction. More detailed investigation into causal mechanisms of AV block in IPAH could establish whether improved prognosis could be achieved by treatment of AV block. FUNDunding Acknowledgement: Type of funding sources: None.